Prostate stem-cell antigen gene is associated with diffuse and intestinal gastric cancer in Caucasians: results from the EPIC-EURGAST study. - Sala, N; Muñoz, X; Travier, N; Agudo, A; Duell, E; Moreno, V; Overvad, K; Tjonneland, A; Boutron-Ruault, M; Clavel-Chapelon, F; Canzian, F; Kaaks, R; et al. (2012)
A genome-wide study performed in a Japanese population identified a strong association between SNP rs2294008 (Met1Thr) in the Prostate Stem Cell Antigen gene (PSCA) and diffuse-type gastric cancer (GC). This association was validated in different Asian populations, and, very recently, a study has been published in Caucasians. In this study, we analyzed the association between PSCA variation and GC risk in Caucasians from the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Six tagSNPs covering the PSCA gene region were genotyped in 411 incident gastric adenocarcinoma cases and 1530 matched controls from a nested case-control study in the EPIC cohort. Associations were analyzed by unconditional logistic regression, adjusting for age, sex and country. The T allele of rs2294008 in PSCA was found to be a highly significant risk factor for GC (per allele OR = 1.42, 95% CI: 1.23-1.66, p-value = 6.5 × 10(-6) ), particularly of the noncardia-type (per allele OR = 1.47, 95% CI: 1.19-1.81, p-value = 3 × 10(-4) ). At contrast with previous studies, no significant differences were observed between the diffuse (per allele OR = 1.54, 95% CI: 1.20-1.96, p-value = 5 × 10(-4) ) and the intestinal (per allele OR = 1.52, 95% CI: 1.20-1.93, p-value = 5 × 10(-4) ) GC histological subtypes. Although rs12155758 and rs9297976 were also found associated with GC, this association appeared to be due to linkage disequilibrium with rs2294008. Haplotype analysis did not provide additional information. These results confirm the association between variation in the promoter region of PSCA and GC risk in Caucasians and also indicate that the rs2294008 variant is a similar risk factor for both the diffuse and intestinal-types of GC.